2022
DOI: 10.1021/acs.orglett.2c00661
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Total Syntheses of C18-Oxo Eburnamine-Vincamine Alkaloids

Abstract: Here, we disclose the divergent total syntheses of representative C18-oxo eburnamine-vincamine alkaloids (+)-eburnaminol, (−)-larutenine, and (−)-cuanzine. Key to the approach is a substrate-controlled iridium-catalyzed asymmetric hydrogenation/lactamization cascade that leads to the formation of the common tetracyclic skeleton with essential cis-C20/C21 stereochemistry (93% yield, 98% ee, >20:1 dr, gram scale). Access to the targeted alkaloids is effected late in the synthesis by implementation of a number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The initial reactions were conducted at a temperature of 25 °C in dichloromethane (DCM) as the solvent, with NaHCO 3 serving as the additive and [Ir(COD)Cl] 2 acting as the catalyst. Following a reaction time of 48 hours, it was observed that (S,S)-f-Binaphane L1, which was the representative ligand for the hydrogenation of unsaturated nitrogenated compounds, 18,31,[33][34][35]44,45 provided the desired product 2a with 91% yield, accompanied by encouraging 2.7 : 1 dr and 69% ee values (Table 1, entry 1). Furthermore, it was observed that the absence of NaHCO 3 resulted in significantly reduced reactivity (entry 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial reactions were conducted at a temperature of 25 °C in dichloromethane (DCM) as the solvent, with NaHCO 3 serving as the additive and [Ir(COD)Cl] 2 acting as the catalyst. Following a reaction time of 48 hours, it was observed that (S,S)-f-Binaphane L1, which was the representative ligand for the hydrogenation of unsaturated nitrogenated compounds, 18,31,[33][34][35]44,45 provided the desired product 2a with 91% yield, accompanied by encouraging 2.7 : 1 dr and 69% ee values (Table 1, entry 1). Furthermore, it was observed that the absence of NaHCO 3 resulted in significantly reduced reactivity (entry 2).…”
Section: Resultsmentioning
confidence: 99%
“…16 Subsequently, they demonstrated an iridium-catalyzed asymmetric hydrogenation of 2-aryl-5-hydroxypyridinium salts to afford trans-2-aryl-piperidin-5-ols with high enantioselectivities (Scheme 1b). 18 As part of our continuous exploration of the synthesis of chiral amines by the AH strategy, 31,[33][34][35][36][37][38] herein, we present our endeavors towards developing an efficient method for the iridium-catalyzed enantioselective and diastereoselective hydrogenation of 2-esteryl-5-hydroxypyridinium salts. This methodology enables access to chiral cis-5-hydroxypiperidine-2-carboxylate esters, which serve as functionalized N-heterocyclic building blocks encompassing three distinct functional groups that were previously challenging to synthesize using conventional methods (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, complete hydrogenation of arenes is one of the most effective methods for converting planar molecules into saturated three-dimensional structures, which are critical building blocks in many aspects of life. 20,21 As part of our continuous interests in the synthesis of chiral amines via AH, [22][23][24][25][26][27] herein, we disclose the first suc-cessful application of iridium-catalyzed complete AH for synthesizing a diverse range of fully saturated chiral hexahydropyrimidines from pyrimidinium salts without using any additional additives. Furthermore, application of this methodology was conducted successfully under continuous flow conditions (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, efficient synthesis of eburnane alkaloids has been the subject of several recent reports. Particular focus has been given to eburnane alkaloids bearing an ethyl side chain, with the most efficient approach recently outlined by Stoltz. , However, the extant approaches pertain mainly to a single subfamily of two–three eburnane alkaloids: a comprehensive approach is still lacking . There is only one strategy regarding the coveted anticancer C19-oxo eburnane alkaloid, described by Trost .…”
Section: Introductionmentioning
confidence: 99%